Morphological discriminations of arius species (siluriformes: ariidae) in Peninsular Malaysia using Truss network approach - Abdurahman, Siti Waznah; Ambak, Mohd Azmi; Mohamed, Ahmad Azfar; Khan Chowdhury, Ahmed Jalal; Ying Giat, Seah (2015)
Ariid catfishes, belongs to family Ariidae is considered as one of the taxonomically problematic group and still under review by fish taxonomist globally. A vigilant and detail observation is important during the species level identification of ariids. Therefore, this study was carried out to determine the morphological variations of one of the ariid genus, Arius, which have been giving misleading taxonomic information in the south-east Asian countries. A truss network technique was used throughout the study period. The study was conducted based on 20 truss distances using 22 to 25 specimens per species. Morphological variations were determined using a multivariate technique of discriminant function analysis (DFA). The results obtained showed a clear separations of all the species in Arius group. Several important morphological characters have been identified, which represent body depth and body length of the fish. The documentary evidences of these variables could be considered as the constructive functional features, which could enable us to assess more accurately distinguish the species within this complex Ariidae family.